Advances and complications of regenerative medicine in diabetes therapy - Olga Brovkina; Erdem Dashinimaev (PeerJ, 2020)
The rapid development of technologies in regenerative medicine indicates clearly that their common application is not a matter of if, but of when. However, the regeneration of beta-cells for diabetes patients remains a complex challenge due to the plurality of related problems. Indeed, the generation of beta-cells masses expressing marker genes is only a first step, with maintaining permanent insulin secretion, their protection from the immune system and avoiding pathological modifications in the genome being the necessary next developments. The prospects of regenerative medicine in diabetes therapy were promoted by the emergence of promising results with embryonic stem cells (ESCs). Their pluripotency and proliferation in an undifferentiated state during culture have ensured the success of ESCs in regenerative medicine. The discovery of induced pluripotent stem cells (iPSCs) derived from the patients’ own mesenchymal cells has provided further hope for diabetes treatment. Nonetheless, the use of stem cells has significant limitations related to the pluripotent stage, such as the risk of development of teratomas. Thus, the direct conversion of mature cells into beta-cells could address this issue. Recent studies have shown the possibility of such transdifferentiation and have set trends for regeneration medicine, directed at minimizing genome modifications and invasive procedures. In this review, we will discuss the published results of beta-cell regeneration and the advantages and disadvantages illustrated by these experiments.